Sigmoid volvulus in children: a case report - Fayza Haider; Nabeel Al Asheeri; Barrak Ayoub; Eizat Abrar; Jawad Khamis; Hasan Isa; Husain Nasser; Fatima Al Hashimi (Journal of Medical Case Reports, 2017)
Abstract Background Sigmoid volvulus is frequently reported in the “volvulus belt” (Middle East, Africa, the Indian subcontinent, Turkey, and South America) and is the third leading cause of large bowel obstruction in North America. It is an uncommon problem in children and adolescents, and is rarely considered a diagnosis in this group. A high index of suspicion is necessary to diagnose sigmoid volvulus in children. Case presentation We present a 13-year-old Arabian girl who came with features suggestive of intestinal obstruction. Plain abdominal film revealed classic omega (coffee bean) sign of sigmoid volvulus. The volvulus was successfully decompressed by means of a rectal tube in our emergency department. The next day during the same admission the volvulus recurred and was successfully decompressed by endoscopy. She was discharged home on her parents’ request; she presented again 1 month later. This time the volvulus could not be decompressed non-operatively, so she underwent sigmoidectomy with primary anastomosis. Postoperatively she developed paralytic ileus that resolved after 10 days. Following that she did well and was discharged home. She is still free of symptoms 1 year after the resection. Conclusions Sigmoid volvulus is an uncommon problem in children and adolescents, and is rarely considered a diagnosis in this group as a cause of intestinal obstruction. Pediatric surgeons should maintain a high index of suspicion, in order not to miss this important diagnosis, as any delay in instituting treatment has a devastating effect on morbidity as well as mortality. Early diagnosis and prompt treatment confer an excellent prognosis.